INFLUENCE OF FRIENDSHIP ENVIRONMENT ON DIEGO PERSONALITY IN THE FILM ENTITLED ICE AGE: A BEHAVIORIST APPROACH - ALFAST, SEVENTEEN TITAN VANADIA (2011)
The major problem of this research is what the influence of friendship reflected on major character. The objective of the study is to analyze the film based on its structural elements and to analyze the film based on behaviorism analysis. In analyzing Ice Age film, the writer uses behaviorism approach and qualitative method. The object of the study is the personality of major character in Ice Age released in 2002. The data sources are literary data divided into two categories, primary data and secondary data. The primary data source is Ice Age Film itself and the secondary data source is other sources related to the data analysis. The method of data collection of the study is library research. The technique of data analysis is descriptive analysis. There are two results of the study; the first result comes from structural analysis. The structural elements in the film include character and characterizations, plot, point of view, mise_en_scene, sound, theme, style, cinematography and the last is editor. The analysis shows that each of the elements are interrelated to each other. Therefore it makes easier to the reader in understanding the story of the Ice Age film. The second result comes from behavior analysis; the study shows that the influence on major character gives the positive impact of his personality. Therefore it makes him more comfortable in his life.